Mentoring on PESTEL Strategy and SWOT Analysis for KADIN Kota Bandung’s MSMEs to Enhance Digital Transformation - Asmara, Maisa Azizah; Ferdiansyah, Fahmi Reza; Rozak, Abdul; Sabila, Sherly Nur; Rizal, Muhammad Khoerul; Aprila, Dikri Sillmi; Buchori, Akbar (Jurnal Pengabdian UNDIKMA, 2024)
This community service program aims to enhance the competitiveness of MSMEs through the implementation of digital transformation, PESTEL strategies, and SWOT analysis, as well as the development of digital marketing capabilities. Additionally, this program seeks to boost the confidence of MSME entrepreneurs under the guidance of KADIN Kota Bandung in achieving economic independence. The methods used include counseling and mentoring, focusing on increasing the participants’ understanding of business strategies and their practical application. The evaluation instrument used is a questionnaire, and the data analysis technique involves quantitative analysis through descriptive statistics to assess the Likert scale-based responses, aimed at comparing pre-test and post-test results. As a result, participants’ comprehension of PESTEL, SWOT strategies, and digital transformation improved significantly. MSMEs were able to identify both external and internal factors for strategic planning, and they became more prepared to adopt digital technologies to enhance business efficiency and innovation. This training provides a comprehensive strategic foundation for the growth of MSMEs in the digital era.